Design and Implementation of Safety and Health Monitoring System for Women - R, Ujwala; HM, Poojashree; YV, Rachana; KV, Vandana; Panda, Subodh Kumar (International Journal of Computer Sciences and Engineering, 2019)
Women security is a major concern and has become mandatory now-a-days. IT companies are looking forward to security solutions for women working at night shifts. This paper proposes a model that can be used to deal with the security issues of working women by tracking location, providing self-defense and alerting people. This proposed system also consists of a health monitoring system to monitor the heart rate and temperature of a person.